Innovative Microcapsules for Pancreatic ß-Cells Harvested from Mature Double-Transgenic Mice: Cell Imaging, Viability, Induced Glucose-Stimulated Insulin Measurements and Proinflammatory Cytokines Analysis - Mooranian, Armin; Takechi, Ryu; Jamieson, E.; Morahan, G.; Al-Salami, Hani (AAPS, 2017)
Purpose: Recently we demonstrated that microencapsulation of a murine pancreatic ß-cell line using an alginate-ursodeoxycholic acid (UDCA) matrix produced microcapsules with good stability and cell viability. In this study, we investigated if translation of this formulation to microencapsulation of primary ß-cells harvested from mature double-transgenic healthy mice would also generate stable microcapsules with good cell viability. Methods: Islets of Langerhans were isolated from Ngn3-GFP/RIP-DsRED mice by intraductal collagenase P digestion and density gradient centrifugation, dissociated into single cells and the ß-cell population purified by Fluorescence Activated Cell Sorting. ß-cells were microencapsulated using either alginate-poly-l-ornithine (F1; control) or alginate-poly-l-ornithine-UDCA (F2; test) formulations. Microcapsules were microscopically examined and microencapsulated cells were analyzed for viability, insulin and cytokine release, 2 days post-microencapsulation. Results: Microcapsules showed good uniformity and morphological characteristics and even cell distribution within microcapsules with or without UDCA. Two days post microencapsulation cell viability, mitochondrial ATP and insulin production were shown to be optimized in the presence of UDCA whilst production of the proinflammatory cytokine IL-1ß was reduced. Contradictory to our previous studies, UDCA did not reduce production of any other pro-inflammatory biomarkers. Conclusions: These results suggest that UDCA incorporation improves microcapsules’ physical and morphological characteristics and improves the viability and function of encapsulated mature primary pancreatic ß-cells.